Highly-stable black phosphorus field-effect transistors with low density of oxide traps - Yu. Yu. Illarionov (Nature Portfolio, 2017)
Electronics: encapsulated black phosphorous enables stable, long-lasting transistors Field effect transistors made of ultra-thin black phosphorous can retain long-term stability and reproducible electrical characteristics. A team led by Prof. Deji Akinwande at UT Austin developed a conformal encapsulation method of black phosphorous transistors with a 25 nm thick Al2O3 layer. Characterization of these devices by Dr. Yury Illarionov at TU Wien has shown that encapsulation results in a substantial improvement of device stability and reliability for at least 17 months in ambient conditions. The density of oxide traps that would cause deleterious variations of the device threshold voltage, thus hindering reproducibility, is as low as 1017 cm−3/eV at room temperature. This is comparable to values obtained for commercial silicon devices. Remarkably, the subthreshold slope of the black phosphorous field-effect transistors becomes steeper after several months, a signature of performance improvement that points towards a positive aging effect, despite extended storage and operation in the laboratory environment.